Pengaruh retapi Hu Care terhadap perawatan diri pada orang dengan Diabetes Mellitus Tipe 2 Di RS Nur Hidayah Bantul Yogyakarta. - Laely Widiyawati (FKU 14 UMY 142, 2014)
Diabetes mellitus is a chronic degenerative disease that progressive and tend to be followed by complications that require special attention. The important factor is self-care that works to expand knowledge and improve patient confidence in the fight against diabetes mellitus and to prevent complications. This can be reinforced by spiritual therapies, such as Hu Care therapy. Hu Care therapy is a non- pharmacological therapy aimed to improve faith and patient’s worship to God. This study used quasi-experimental method to determine the effectivity of Hu Care therapy on self-care activity amongtype 2 diabetes patients. Number of samples in this study were 22 subjects, 11 subjects as the experimental group and 11 subjects as a control group. Self-care were assessed before and after Hu Care therapy using a questionnaire. The results obtained were processed using SPSS with Independent Sample Test. The results showed that Hu Care therapy is significantly effective in improving self-care of patients with type 2 diabetes. This is indicated by the value of p = 0.000 (p < 0:01). Keywords : Hu Care Therapy, Self-care , Type 2 Diabetes